On Homomorphisms of Algebras Generated by Projectors and Coxeter Functors - Popovich, S. V.; Samoilenko, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We consider algebras generated by idempotents in Banach spaces and orthoprojectors in Hilbert spaces whose sum is a multiple of the identity. We construct several functors generated by homomorphisms of the algebras considered between categories of representations. We investigate properties of these functors and present their applications.